1999
DOI: 10.1074/jbc.274.45.32382
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia Enhances Angiotensin II-induced Janus-activated Kinase/STAT Signaling in Vascular Smooth Muscle Cells

Abstract: We have shown previously that angiotensin II (Ang II) activates the janus-activated kinase (JAK)/signal transducers and activators of transcription (STAT) pathway in vascular smooth muscle cells (VSMCs) and that activation of the JAK/STAT pathway is required for Ang II induction of VSMC proliferation. In the present study, we examined the effects of hyperglycemia (HG) on Ang II-induced JAK/STAT signaling events in cultured VSMCs. HG increases Ang II-induced JAK2 tyrosine phosphorylation and promotes a partial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 19 publications
3
55
1
Order By: Relevance
“…We have S100B ACTIVATES JAK2 VIA PLD2 previously shown that activation of JAK2 is required for Ang II-mediated induction of VSMC proliferation and that high glucose augments both Ang II-induced activation of JAK2 and VSMC proliferation (10,19). Since formation of AGEs is accelerated by hyperglycemia and oxidant stress, as in diabetes (20,21), we examined the effects of RAGE activation on JAK2 signaling by using the well-characterized ligand S100B.…”
Section: Resultsmentioning
confidence: 99%
“…We have S100B ACTIVATES JAK2 VIA PLD2 previously shown that activation of JAK2 is required for Ang II-mediated induction of VSMC proliferation and that high glucose augments both Ang II-induced activation of JAK2 and VSMC proliferation (10,19). Since formation of AGEs is accelerated by hyperglycemia and oxidant stress, as in diabetes (20,21), we examined the effects of RAGE activation on JAK2 signaling by using the well-characterized ligand S100B.…”
Section: Resultsmentioning
confidence: 99%
“…7 Hyperglycemia has been shown to promote cellular growth and proliferation and increase production of extracellular matrix proteins in MCs and vascular smooth muscle cells. 14,26,27 The progrowth and proliferative effects of high glucose appear to be mediated by activation of the MAPKs, including ERK 1/2, c-Jun N-terminal kinase, and p38. 14,26 -28 However, direct effects of glucagon on MC proliferation and activation of ERK 1/2 have not been reported to our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…The altered state of SHP2 hinders its ability to interact with JAK2 [44] . In hyperglycemic states, SHP2 levels and activity display a two-fold increase in VSMCs compared with the normal glucose environment [45] .…”
Section: Shp2 and Jak/statmentioning
confidence: 99%